One Health Approach in Serosurvey of Toxoplasma gondii in Former Black Slave (Quilombola) Communities in Southern Brazil and Among Their Dogs - Giovanni Kalempa Panazzolo; Louise Bach Kmetiuk; Orlei José Domingues; João Henrique Farinhas; Fernando Rodrigo Doline; Danilo Alves de França; Nássarah Jabur Lot Rodrigues; Leandro Meneguelli Biondo; Rogério Giuffrida; Helio Langoni; Vamilton Alvares Santarém; Alexander Welker Biondo; et al. (Tropical Medicine and Infectious Disease, 2023)
Brazilian quilombos are rural semi-isolated remnant communities of former black slaves and their descendants who traditionally maintained themselves through archaic subsistence livestock and agriculture practices and historically lacked specific public health policies. Although such individuals and their dogs may be exposed to zoonotic pathogens such as Toxoplasma gondii, no study to date has assessed these human-animal populations together. Populations in four different Brazilian quilombos in southern Brazil were evaluated. Overall, 93/208 people (44.7%) and 63/100 dogs (63.0%) were seropositive for IgG anti-T. gondii antibodies by indirect immunofluorescent antibody test (IFAT), 4/208 (1.9%) human samples seropositive for IgM anti-T. gondii antibodies, with a human-dog seropositivity ratio for IgG of 0.71. Quilombola individuals ingesting game meat were 2.43-fold more likely (95% CI: 1.05–5.9) to be seropositive. No risk factors were associated with seropositivity among dogs, thus suggesting that their exposure to T. gondii was random. Surprisingly, our research group had previously found an inverted human-dog ratio for T. gondii seropositivity of 2.54 in the urban area of a nearby major city. Because consumption of raw/undercooked game meat by quilombola individuals may have contributed to higher exposure, higher overall seroprevalence among dogs may have also indicated interaction with wildlife. Although these dogs may hunt wildlife without their owners’ awareness, the higher dog seropositivity may also be related to feeding from discarded food in the community or backyard livestock animals and drinking surface water contaminated with oocysts. Thus, wildlife cannot be singled out as the reason, and future studies should consider sampling water, soil, wildlife, and livestock tissues, to fully establish the source of infection in dogs herein.